2011
DOI: 10.1161/strokeaha.110.606558
|View full text |Cite
|
Sign up to set email alerts
|

Trigger Factors and Their Attributable Risk for Rupture of Intracranial Aneurysms

Abstract: Background and Purpose-Little is known about activities that trigger rupture of an intracranial aneurysm. Knowledge on what triggers aneurysmal rupture increases insight into the pathophysiology and facilitates development of prevention strategies. We therefore aimed to identify and quantify trigger factors for aneurysmal rupture and to gain insight into the pathophysiology. Methods-During a 3-year period, 250 patients with aneurysmal subarachnoid hemorrhage completed a structured questionnaire regarding expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
130
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(132 citation statements)
references
References 28 publications
2
130
0
Order By: Relevance
“…The evidence on recent infection in relation to the incidence of SAH is limited. 14,24,30,52,58 The results of a Canadian study from the Calgary region were comparable with our findings and showed a small but significant increase in the incidence of SAH during influenza epidemics, with a delay between increased influenza and SAH rates of 0.9 week. 14 A case-control study found that an upper respiratory tract infection was an independent trigger factor for SAH, but this study included only 44 patients.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The evidence on recent infection in relation to the incidence of SAH is limited. 14,24,30,52,58 The results of a Canadian study from the Calgary region were comparable with our findings and showed a small but significant increase in the incidence of SAH during influenza epidemics, with a delay between increased influenza and SAH rates of 0.9 week. 14 A case-control study found that an upper respiratory tract infection was an independent trigger factor for SAH, but this study included only 44 patients.…”
Section: Discussionsupporting
confidence: 88%
“…These changes lead to an increase in blood pressure, 26,35 which in turn may trigger aneurysm rupture. 58 A strength of our nationwide study is that the catchment area during the study period did not change. Also, the sample size was large because we used nationwide data on the incidence of SAH and influenza-like illness.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mukamal and his colleagues [27] used this approach to compare measures of weather and ambient air pollution on the day of stroke presentation and on other days (as control) for each patient. Vlak [28] applied case-crossover design to identify trigger factors for rupture of intracranial aneurysms.…”
Section: Problem and Data Specificationmentioning
confidence: 99%
“…Although hypertension is a classic factor that contributes to the rupture of cerebral aneurysms (Obray et al, 2003;Vlak et al, 2011), there is no consensus concerning the effects of CAS on the course of unruptured intracranial aneurysms. However, intracranial hemorrhages are associated with high morbidity and high mortality during the treatment of carotid artery stenosis (Cheung et al, 2003;Hartmann et al, 2004).…”
Section: The Association Of Carotid Stenosis With Cerebral Aneurysmsmentioning
confidence: 99%